Pengaruh Kualitas Pelayanan Harga Dan Fasilitas Terhadap Kepuasan Konsumen(Studi Pada Pasien Rumah Sakit Karima Utama Surakarta) - Dwi Hanggono, Danar; , Drs. Farid Wajdi, MM, Ph.D (2017)
The aim of this study was to analyze the influence of service quality, price, and customer satisfaction at the facilities of the RS Main Karima Surakarta. This type of research is quantitative. Samples of this research is patient Karima Hospital Surakarta Top 100 respondents with sampling technique. purposive sampling Methods of data collection using questionnaires. Data were analyzed using analysis instrument test data, the classical assumption test, multiple linear regression. Based on the calculation of the t-test, F shows the variable quality of service, price, and amenities together with significant influence on customer satisfaction. Coefficient Determination R2 obtained a yield of 0.629 means that the variable quality of service, price, and amenities were able to explain the variation of the variable changes in consumer satisfaction by 62.9%, the rest can be explained other variables that are not included in the research model.